Impact of Covid-19 Vaccination and Financial Policies on Indonesia’s Property Loan Growth - Forestryani, Veniola; Prastyo, Dedy Dwi (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Research Originality: This study provides a novel examination of the impact of COVID-19-related financial policies on property loan growth in Indonesia, a critical area with limited prior quantitative research.Research Objectives: The purpose of this research is to assess how interventions such as Loan-to-Value (LTV) over Finance-to-Value (FTV) ratio (LTV/FTV) relaxation, COVID-19 vaccination as a metric for public activity restrictions, and changes in deposit insurance rates have influenced property loan dynamics during the pandemic.Research Methods: Using monthly banking data from January 2016 to May 2022, this study employs ARIMA Intervention Analysis to capture the effects of these policies.Empirical Results: The empirical results reveal a significant positive shift in property loan growth ten months after the first intervention and a notable impact two months after the third intervention, whereas the second intervention shows limited influence.Implications: These findings imply that integrating COVID-19 vaccination targets into public policy and adjusting deposit insurance rates are effective strategies for sustaining the property loan sector during economic crises. These results provide insights into the role of vaccination targets and financial adjustments in supporting the property loan sector during economic disruptions, offering valuable considerations for future policymaking in similar contexts.JEL Classification: C22, C51, C52, C53, C54